Design and multi-step synthesis of chalcone-polyamine conjugates as potent antiproliferative agents. Issue 18 (15th September 2017) - Rioux, Benjamin; Pouget, Christelle; Fidanzi-Dugas, Chloë; Gamond, Aurélie; Laurent, Aurélie; Semaan, Josiane; Pinon, Aline; Champavier, Yves; Léger, David Y.; Liagre, Bertrand; Duroux, Jean-Luc; Fagnère, Catherine; et al.
Graphical abstract: Abstract: The aim of this study is to synthesize chalcone-polyamine conjugates in order to enhance bioavailability and selectivity of chalcone core towards cancer cells, using polyamine-based vectors. 3-hydroxy-3′, 4, 4′, 5′-tetramethoxychalcone (1 ) and 3′, 4, 4′, 5′-tetramethoxychalcone (2 ) were selected as parent chalcones since they were found to be efficient anti-proliferative agents on various cancer cells. A series of ten chalcone-polyamine conjugates was obtained by reacting carboxychalcones with different polyamine tails. Chalcones1 and2 showed a strong cytotoxic activity against two prostatic cancer (PC-3 and DU-145) and two colorectal cancer (HT-29 and HCT-116) cell lines. Then, chalcone-spermine conjugates7d and8d were shown to be the most active of the series and could be considered as promising compounds for colon and prostatic cancer adjuvant therapy.